SHORT FICTIVE REFLECTIONS ON THE PERCEPTION OF A POSTSECONDARY EXPERIENCE OF LONG-TERM INCARCERATED JUVENILES - Barraza, Gregory (Art/Research International, 2021)
There is a gap in the literature regarding postsecondary opportunities for incarcerated youth. Research and curriculum design are rarely available for the purpose of improving juvenile postsecondary correctional education thereby not improving recidivism rates of formerly incarcerated students. The pilot program in this study attempted to provide a comprehensive university program for long-term incarcerated juveniles to get them on track to obtain a bachelor’s degree. This study addressed the academic experiences, including the School to Prison Pipeline and the academic experience to provide information, justifying the importance of creating postsecondary academic opportunities for incarcerated juveniles. Then, the study analyzed interviews with recently released students of the program to give insight to correctional education experiences vis-à-vis artistic representations, in this case, short fiction. This article presents fictive artistic representations that give a closer look at the secondary and postsecondary educational experiences of two of the cohort participants.